Use of reserve antibiotics in patients of the main services of the Hospital Uldarico Rocca Fernandez - EsSalud - Simón Quilca, Hilaria (2019)
Objective: To determine the consumption of reserve antibiotics in adult patients in the main services of the Hospital Uldarico Rocca Fernandez - EsSalud, in the first semester of 2018. Materials and Methods: It was an observational, descriptive study where the study units were 894 prescriptions of all patients hospitalized in the main services of the Hospital Uldarico Rocca Fernandez attended within the 1st semester of the year 2018. Results: The results showed that ceftriaxone was the most used reserve antibiotic in the three hospitalization services: Surgery, Intensive Care and Medicine. Conclusion: It is concluded that 38% of hospitalized patients were treated with antibiotics and 54% used ceftrioaxone; therefore, a greater control measure is recommended for the use of antibiotics as the therapeutic group and the medic prescription must to be according to their pathology to avoid the irrational use of such antibiotics.